2017
DOI: 10.2106/jbjs.17.00031
|View full text |Cite
|
Sign up to set email alerts
|

Graduation Protocol After Growing-Rod Treatment: Removal of Implants without New Instrumentation Is Not a Realistic Approach

Abstract: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 11 publications
2
28
0
3
Order By: Relevance
“…5,6 In 2017 Kocyigit et al 3 mentioned a comparative study in patients treated with growing rods, and they concluded that in patients who achieved skeletal maturity, rod removal without new instrumentation is an unacceptable treatment because it leads to a worsening of the deformity. The results in the 2 presented cases confirm the conclusions of Kocygit et al 3 Despite observing, after the rods' removal, an acceptable and satisfying final correction (508), skeletal maturity (Risser 5), and the appearance of secondary sexual characteristics, we also observed a rapid progression of the deformity. Because of this experience, some observations are needed.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…5,6 In 2017 Kocyigit et al 3 mentioned a comparative study in patients treated with growing rods, and they concluded that in patients who achieved skeletal maturity, rod removal without new instrumentation is an unacceptable treatment because it leads to a worsening of the deformity. The results in the 2 presented cases confirm the conclusions of Kocygit et al 3 Despite observing, after the rods' removal, an acceptable and satisfying final correction (508), skeletal maturity (Risser 5), and the appearance of secondary sexual characteristics, we also observed a rapid progression of the deformity. Because of this experience, some observations are needed.…”
Section: Discussionsupporting
confidence: 90%
“…EOS treatment with Magec rods has been established, but patient management at the end of the lengthening period, until skeletal maturity, remains controversial. In the literature, the reported options 3 are the rods' removal followed by patient observation, rods' removal and immediate instrumented fusion, or rod maintenance/replacement. We present 2 cases of EOS patients treated with Magec rods (NuVasive Specialized Orthopedics Inc, Aliso Viejo, CA) up to skeletal maturity.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, Kocyigit et al ask the important question of whether avoiding final fusion can be taken a step further with the removal of growing rods [12]. The authors hypothesize that autofusion results in enough stability to prevent further curve progression.…”
Section: Commentarymentioning
confidence: 99%
“…Given the numerous challenges of management at the conclusion of growing rod treatment, authors of a recent study examine the option of removing the growing rods without subsequent fusion. This article describes a single-center prospective cohort study of 26 children who underwent growing rod treatment when they were 10 years old or younger [12]. The authors used an institutional database to identify 86 patients with traditional growing rods.…”
Section: Introductionmentioning
confidence: 99%
“…For TGRs, one study suggested that only 38% (10/26) patients at skeletal maturity are suitable for implant removal without spinal fusion. 71 However, nine of these patients had progression of the deformity after implant removal resulting in an additional surgery for fusion. Whether patients can or should remove their MCGRs without fusion or whether every patient needs final fusion should be studied.…”
Section: Moving Forwardsmentioning
confidence: 99%